The Types of Ownership and Sticky Cost: Evidence from Listed Firms of Indonesia Capital Market - Meythi, Meythi; Martusa, Riki; Candra, Anastasya Regina (Jurnal Keuangan dan Perbankan, 2023)
This study examines whether ownership structure type of listed banks of Indonesia Stock Exchanges (IDX), especially State of Owned Banks (SOBs) affect to cost stickiness. This study observes listed state-owned banks during the periods of 2001-2020. This study finds that ownership structure type of listed banks of IDX, i.e. SOBs, affects to cost stickiness are not supported. However, cost stickiness of listed SOBs of IDX relates to asset and employee are supported. However, a SOBs purpose to profit-oriented, but they also commit to government programs, i.e. reducing unemployment and expanding job opportunities. Overall, the findings of this study indicate that SOBs do not influence cost stickiness, but there are differences between high and low asset and employee SOBs. This study contributes to literatures of financial accounting and finance in banking sector, particularly SOBs.JEL: M410, C12, L52*